Dwa listy Kazimierza Przerwy Tetmajera do Józefa Jankowskiego - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article is an editorial work on two letters from Kazimierz Przerwa Tetmajer to a catholic poet and journalist, Józef Jankowski. The letters complement to some extent the biographical knowledge about Tetmajer, especially his participation in the literary life of the Young Poland and the interwar period.